Feto-maternal outcome in second versus first stage caesarean delivery in a tertiary medical care centre - Gupta, Nupur; Gupta, Taru; Singh, Ritu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim is to study neonatal and maternal outcomes of the caesarean sections performed in first stage versus second stage of labour. Methods: The retrospective analysis of data were done of caesarean section done at Department of Obstetrics and Gynaecology at ESI PGIMSR Basaidarapur New Delhi between January 2016 to December 2016. 45 women, who underwent second stage caesarean section were studied. For each case, two consecutive cases, who underwent caesarean delivery during the first stage of labour were taken as control for the study. Primary maternal outcomes of interest were uterine atonia, transfusion requirement, urinary system injury and postoperative complications. Results: Out of 4477 deliveries, 1466 had caesarean section with a rate of 32%. The rate of second stage caesarean section was 3% of total caesarean section and 1% of total deliveries. Second stage caesarean section had higher maternal and perinatal morbidity like atonic PPH (33.3%), lower uterine segment extension (7%), febrile morbidity (10%), and need for blood transfusion (15%). There were 15.5% NICU admission in second stage caesarean group while none in first stage group. Conclusions: Caesarean section in the second stage of the labour is associated with increased maternal and neonatal morbidities. Special attention is required to the patients undergoing caesarean section in the second stage of the labour. They should be handled by senior and experienced obstetrician. Neonatologist should be present for every second stage caesarean section. <!–[if gte mso 9]> Normal 0 false false false EN-IN X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>